2014
DOI: 10.1021/bm401714v
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glycogen Structure over Feeding Cycle Sheds New Light on Blood-Glucose Control

Abstract: Liver glycogen, a highly branched polymer of glucose, is important for maintaining blood-glucose homeostasis. It was recently shown that db/db mice, a model for Type 2 diabetes, are unable to form the large composite glycogen α particles present in normal, healthy mice. In this study, the structure of healthy mouse-liver glycogen over the diurnal cycle was characterized using size exclusion chromatography and transmission electron microscopy. Glycogen was found to be formed as smaller β particles, and then onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…An in vitro study [56] with rabbit-liver glycogen supports this hypothesis, with glycogen phosphorylase having a higher activity for smaller molecules in the direction of glycogen synthesis. In 1971 Geddes [16] also found that Replotted from data in Sullivan et al [50] glucose tended to be incorporated more into lower-weight material, which is consistent with smaller molecules being synthesised more rapidly. The second major insight resulting from the structural study of glycogen across a diurnal cycle is that towards the end of glycogen degradation, there is a much greater proportion of large a-particles remaining.…”
Section: Implications For Human Healthmentioning
confidence: 78%
See 1 more Smart Citation
“…An in vitro study [56] with rabbit-liver glycogen supports this hypothesis, with glycogen phosphorylase having a higher activity for smaller molecules in the direction of glycogen synthesis. In 1971 Geddes [16] also found that Replotted from data in Sullivan et al [50] glucose tended to be incorporated more into lower-weight material, which is consistent with smaller molecules being synthesised more rapidly. The second major insight resulting from the structural study of glycogen across a diurnal cycle is that towards the end of glycogen degradation, there is a much greater proportion of large a-particles remaining.…”
Section: Implications For Human Healthmentioning
confidence: 78%
“…[45,49] This striking difference between non-diabetic and diabetic glycogen has highlighted the importance of understanding glycogen metabolism in terms of structure. A recent study [50] has used SEC to analyse the structure of mouse-liver glycogen at various time points in the feeding cycle, exploiting the natural diurnal rhythm of liver glycogen metabolism in mice. [47,[51][52][53][54] As has been previously reported, [47,55] liver glycogen was synthesised in the dark hours and subsequently degraded in the hours of light (see Fig.…”
Section: Implications For Human Healthmentioning
confidence: 99%
“…Differently from skeletal muscle glycogen, these larger particles with a proportionally lower protein content [9] would be in line with a slower mobilization of glucosyl units for hepatic glucose output during progressive fasting. Interestingly, the formation of aparticles in the liver appears to occur during net glycogen degradation, providing a mechanism to control glucose release [12,13].…”
Section: Glycogen Biochemistry Structure and Functionmentioning
confidence: 99%
“…Those in Group 1 were sacrificed in the morning, between 9 and 10 am, and those in Group 2 were sacrificed in the afternoon between 2 to 3 pm. These two times are respectively at the beginning and end of the degradation phase in glycogen synthesis [14]. Rats were anaesthetized with sodium pentobarbitone (150 mg/kg intraperitoneal) and their livers were rapidly excised and divided into six parts according to the lobe sections given in Fig.…”
Section: Excision Of Livermentioning
confidence: 99%
“…The liver-glycogen content was analyzed using a method reported elsewhere [14,16]. Liver homogenates from Group 1 (sacrificed in the morning) were used for glycogen content assay.…”
Section: Glycogen Contentmentioning
confidence: 99%